Ultrasound‐assisted lumbar puncture in Alzheimer's disease and related disorders research: A pilot study. (31st December 2021) - Goldfarb, Danielle; Viramontes, Daniel; Callan, Michael; Liebsack, Carolyn; Goddard, Molly; Reade, Marina; Malek‐Ahmadi, Michael H.; Weidman, David; Tsai, Po‐Heng; Wu, Teresa; Grimsman, Jason; Atri, Alireza
Abstract: Background: Lumbar puncture (LP) and collection of cerebrospinal fluid (CSF) are increasingly essential in Alzheimer's disease and related disorders (ADRD) research. Ultrasound‐assisted lumbar puncture (Us‐LP) has not been studied in ADRD research and could improve LP success rates through more accurate anatomical site selection, precise planning, and individualized intra‐procedure adjustments. This pilot study assessed the feasibility, utility, and tolerability of Us‐LP in ADRD research. Method: LP clinician‐researchers from ADRD centers completed simulation‐based Us‐LP training using the Philips Lumify system, a portable hand‐held transducer connecting to a tablet. Thereafter, clinician‐researchers had the option to use Us‐LP during research LPs. Participant demographics and attitudes about LP were obtained prior to LP. The clinician‐researchers completed a post‐LP questionnaire assessing procedural details, choices, and LP performance. Result: Following training, four clinician‐researchers implemented Us‐LP into their practices. Between August 2019‐March 2020, 58 research participants (Table 1) underwent LP. Clinician‐researchers used Us‐LP on 37/58 (64%) participants. Compared to conventional‐LP, Us‐LP choice was associated with higher/highest BMI and older/oldest age categories (Tables 2, 3). A U‐shaped relationship between BMI and Age in Us‐LP choice was noted (Figure 1). Us‐LP was also the choice in all who were most obese; in most who were moderately overweight‐to‐obese; and in all who were oldest and moderately overweight‐to‐obese. There were no differences between those receiving conventional‐LP compared to US‐LP with respect to participant history of chronic pain or headache, prior attitudes about LP, success rate, or post‐LP complications. Conclusion: Training clinician‐researchers in Us‐LP and implementing portable hand‐held Us‐LP for ADRD research studies demonstrated feasibility, utility and tolerability. Pilot data indicated that clinician‐researchers were more likely to use Us‐LP in perceived challenging cases including the most obese, and those oldest and moderately overweight‐to‐obese. More studies are needed to determine if using Us‐LP in ADRD research will improve LP success rates, tolerability, and participant willingness to undergo LP. Improving these factors will accelerate CSF biomarker, aging and ADRD research. Furthermore, with potential availability of AD disease‐modifying treatments in the coming years, LP and CSF collection are likely to play a crucial role in patient selection for treatment.